New insights into how green innovation, renewable energy, and institutional quality shape environmental sustainability in emerging economies - Gan, Juan (Frontiers in Environmental Science, 2025)
The development of green innovation in achieving Sustainable Development Goals (SDGs) is gaining popularity in recent works. However, the perspective from emerging economies is limited leaving them behind in the drive toward global sustainability. Therefore, this study provides new insights into how green innovation development and the quality of institutions have influenced green energy adoption and overall Sustainability using 30 emerging economies from 1990 to 2020. The study employs three econometric models—Fully Modified Ordinary Least Squares (FMOLS), Dynamic Ordinary Least Squares (DOLS), and Ordinary Least Squares (OLS) to make a comparative analysis. The findings show the varying and pivotal role of technological advancements, institutions, and green energy in reducing carbon footprints based on models. Notably, it was found that green innovation had a positive effect (FMOLS), and negative effect (DOLS and OLS) on CO2 emissions. Renewable energy had a negative effect (FMOLS and OLS), and a positive effect (DOLS) on CO2 emissions. Again, institutional quality showed a positive effect (DOLS and FMOLS) and a negative effect (OLS) on CO2 emissions. The study believes the DOLS model exhibited the most robust explanatory power, with the highest explanatory power of 99.9%. These results provide greater insights and the comprehensive policies outlined can help policymakers formulate working policies to bolster green innovation, improve green energy development, and strengthen institutional frameworks toward achieving overall SDGs.